Impact of female labour force participation on the economic growth: Evidence from Saudi Arabia - Alruwaili, Naif Fawzi; Mokni, Khaled (Zielona Góra: Faculty of Economics and Management Press)
This study investigates the impact of female labor force participation (FLFP) on the economic growth in Saudi Arabia, a country currently implementing extensive socio-economic reforms. We conduct a sectoral and regional analysis using regression techniques on data from 2015 to 2023. Our findings indicate that FLFP has a statistically significant positive effect on the gross domestic product (GDP) across all regions in Saudi Arabia.
Keywords: economic growth; female labour force; regional economic growth